IMPACT OF INFLATION TARGETING POLICY AND MONEY SUPPLY CONTROL ON NIGERIA’S ECONOMIC PERFORMANCE - Keniyinboh Adimiegha Bob; Mojekwu, Ogechukwu Rita; Nwinee, Barisua Fortune (Scholars Digest Publishing, 2025)
This study examines the impact of inflation targeting policy and money supply control on Nigeria’s economic performance over the years 2000-2023. The study relied on various data obtained from CBN statistical bulletin of various issues. Using the ADF test GDP, INFR, INTR and MS were all found to be stationary at first difference. The Vector Error Correction Model (VECM) has been applied to show the relationship among the variables, which reveals a long run relationship. The study concludes that while inflation targeting and money supply control are essential for economic stability, their success depends on stronger policy coordination, fiscal management and addressing structural economic challenges.